Strategi Peningkatkan Kinerja Pegawai Di PD Pasar Horas Jaya Siantar - Ben Setiawan Barus (Information Technology and Science (ITScience), 2019)
The achievement of revenue targets PD Pasar Horas Jaya Siantar were not as expected, of course, shows the performance of PD Pasar Horas JayaSiantar is not optimal. Many factors affect the achievement of revenue targets, one of which is the human factor in this case is no PD Pasar Horas Jaya employee performance. If the employee has a good performance, then the trader as the party renting selling space will be more loyal and have an impact on increasing the occupancy rate of the market. This type of research in this study is correlational research that consists of four independent variables and the dependent variable of employee performance, Analysis of the data used is multiple regression analysis. The result showed that the performance of employees PD Pasar Horas Jaya Siantar by 39.1% influenced by competence, work culture, organizational communication and motivation